Novel propranolol-loaded gastro-floating 3D-printed devices with zero-order release kinetics - Dareena Jaiseri; Supusson Pengnam; Praneet Opanasopit; Tanasait Ngawhirunpat; Theerasak Rojanarata; Prasopchai Patrojanasophon; Teeratas Kansom; Thapakorn Charoenying (Pharmacia)
Currently, fused deposition modeling (FDM) is a 3D printing technology that has been most widely used to develop innovative drug delivery approaches for overcoming the limitations of oral drug administration. Propranolol has a short plasma half-life and is well soluble in acidic environments. Thus, this study aimed to develop a gastro-floating 3D printed device (GFD) to sustain the release of propranolol in the stomach as a gastro-retentive drug delivery system. The polylactic acid (PLA) was selected to fabricate the GFD. An air chamber was included in the interior construction of the GFD design for buoyancy. The number of open channels on the side wall of GFD was modified to regulate release. The propranolol gel formulation was composed of a mixture of propranolol and polyvinylpyrrolidone (PVP) at the weight ratio of 6:5 and was then loaded into GFDs using a syringe. GFD exhibited a floating ability of more than 24 h with low standard deviation (SD) values of weight variation and shape dimension. The propranolol release from GFD shows sustained release properties in the simulated gastric environment without lag time. The 4 and 5 channels of GFD exhibited sustained drug release for 6 h. In addition, the duration of sustained release for 8 h was achieved from the GFD with 2 and 3 channels. The kinetic release of propranolol from GFDs was the best fit with zero-order. Thus, the GFDs could be designed to control the drug release according to each patient, which has the potential for applying personalized gastro-retentive drug delivery in various medications. Graphical abstract